1995
DOI: 10.1002/1361-6374(199503)3:1<1::aid-bio1>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Volume ratios of painted chromosome territories 5, 7 and X in female human cell nuclei studied with confocal laser microscopy and the Cavalieri estimator

Abstract: Chromosome territories 5, 7 and X were painted in female human amniotic fluid or fibroblast cell nuclei with chromosome specific DNA library probes. For probe detection the fluorochromes FITC or TRITC were applied. Using confocal laser scanning fluorescence microscopy ten to twenty light optical sections of FITC or TRITC images were registered with equal spacing (approximately 400 nm) for each of 131 nuclei showing well separated homologous chromosome territories. Chromosome territory areas were segmented appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
1
9
1
Order By: Relevance
“…DNA FISH probes that paint chromosomes have generally been employed to estimate chromosomal volume and through application of this technique, multiple studies using RNA/DNA FISH to identify the Xist RNA-coated Xi, have reported that the volume occupied by the Xi is smaller than that of the Xa. Using the total nuclear volume as a normalizer, a standard ratio of between 1.25 +/− 0.05 is consistently reported [55,94,95]. However, to decisively conclude that the nuclear space occupied by the Xi is indeed smaller than that of Xa, the difference between the Xa and Xi should be compared to, and significantly differ from, that between homologous autosomes.…”
Section: Shape and Volume Distinguish The XI From The Xamentioning
confidence: 99%
See 1 more Smart Citation
“…DNA FISH probes that paint chromosomes have generally been employed to estimate chromosomal volume and through application of this technique, multiple studies using RNA/DNA FISH to identify the Xist RNA-coated Xi, have reported that the volume occupied by the Xi is smaller than that of the Xa. Using the total nuclear volume as a normalizer, a standard ratio of between 1.25 +/− 0.05 is consistently reported [55,94,95]. However, to decisively conclude that the nuclear space occupied by the Xi is indeed smaller than that of Xa, the difference between the Xa and Xi should be compared to, and significantly differ from, that between homologous autosomes.…”
Section: Shape and Volume Distinguish The XI From The Xamentioning
confidence: 99%
“…By conducting this additional normalization step, Rinke and colleagues showed that the average difference in normalized chromosomal volume between X homologs falls within the range observed for autosome pairs. Thus, rather than being caused by increased compaction, the difference in the volume of the Xi compared to the Xa may simply be due to a natural variation in the nuclear space occupied by homologous chromosomes [95]. Since XCI is random, the authors did not distinguish one X-chromosome homologue from another, thus it remains possible that the Xi is indeed consistently smaller than the Xa and that the chance of an autosome occupying a larger volume than its homologue is instead randomly distributed between the two.…”
Section: Shape and Volume Distinguish The XI From The Xamentioning
confidence: 99%
“…The Voronoi volume estimator is given by equations (3.2) and (3.3). The values obtained by the Voronoi volume estimator were compared with the volume estimates obtained by the Cavalieri estimator after a simple thresholding segmentation of each individual serial section (Rinke et al, 1995). Fig.…”
Section: Comparison Of Voronoi and Cavalieri Volume Estimatesmentioning
confidence: 99%
“…The spatial intranuclear distribution of chromosome territories appears to depend on cell type and cell cycle (Billia and DeBoni 1991;Vourc'h et al 1993;Cremer et al 1994;Zalensky et al 1995). The different packaging of the DNA is assumed to be associated to different transcription efficiencies of genes (Gerdes et al 1994;Rinke et al 1995).…”
Section: Introductionmentioning
confidence: 99%